Pneumothorax after Colonoscopy - A Review of Literature - Ajay Gupta; Hammad Zaidi; Khalid Habib (Korean Society of Gastrointestinal Endoscopy, 2017)
The purpose of this study was to determine the anatomical aspects, mechanisms, risk factors and appropriate management of development of pneumothorax during a routine colonoscopy. A systematic search of the literature (MEDLINE, Embase and Google Scholar) revealed 21 individually documented patients of pneumothorax following a colonoscopy, published till December 2015. One additional patient treated at our center was added. A pooled analysis of these 22 patients was performed including patient characteristics, indication of colonoscopy, any added procedure, presenting symptoms,risk factors and treatment given. The review suggested that various risk factors may be female gender, therapeutic interventions, difficult colonoscopy and underlying bowel pathology. Diagnosis of this condition requires a high index of suspicion and treatment should be tailored to individual needs.